Strategic spatial planning through pragmatic blueprints: Forms and levels of adaptivity in modernist planning of the Dutch IJsselmeerpolders. (January 2021) - van Dijk, Terry
Highlights: Urban and regional planning is a strategic policy making process responding to the big challenges of our time. Pleas for more adaptivity when making plans have resulted in a hesitation to act even in countries with a strong planning tradition. This paper shows that the degree of adaptivity can differ between topics, geographical scales and time spans. The case of the Dutch IJsselmeerpolder project illustrates how long-term decisions enable learning cycles of short-term decisions. The land use challenges of our time need the stability of main concepts for the long term that are pragmatically implemented Abstract: Strategic spatial planning is a governance practice pursuing coordinated improvement of mobility, housing, food production and other functions with a spatial impact. The institutions in this practice marry long-term thinking in the light of societal challenges with strategic action. These activities are intertwined, visionary and pragmatic at the same time. The currently prevalent association within strategic planning of long-term polical determination with rigid, top-down blueprints has prompted reduced national and regional planning efforts in the Netherlands and other European countries. Adaptivity and resilience within planning processes are promoted as novel and more suitable ways of steering spatial conditions within societies today. Adaptive is defined as 'being open for reconsideration'. Choices that were considered good yesterday, may need to be reconsidered tomorrow. The notion of adaptivity in planning, and the desirability of it, needs more nuance. Because, (1) Do changing long-term perspectives imply a need for adaptivity in the strategies used? (2) To which precise aspects of deliberate strategies can adaptivity apply? (3) Does the pursuit of adaptivity require a new planning approach, as is often claimed? We applied these questions within a critical case study: the creation of the Dutch IJsselmeerpolders, prototypes of rigid rather than adaptive planning, a strategy pursued for over 50 years. Despite radically shifting long-term perspectives, the governance practice of plan-making appears to have been capable of serving evolving purposes. Within this masterplanned mega-project we identify five forms of adaptivity associated with different geographical and time scales. We conclude that an enduring strategic governance effort can support shifting long-term perspectives when it is applied pragmatically with regard to selected topics. Rigidity and adaptivity are equally indispensable and inevitable for strategic action.